2016
DOI: 10.1001/jamaneurol.2016.3943
|View full text |Cite
|
Sign up to set email alerts
|

JAMA Neurology at the Forefront, 1997-2016

Abstract: ecosystems that simply do not apply to print publishing. Whether readers, authors, institutions, or funders support the costs of publishing, publishing to a contemporary online standard-making medical science discoverable, mobile, consumable, and social-is a complex, full-time, and ongoing program that should be a part of conversations about the standards and costs of how to make science more accessible and open.We have thought through every pixel of every page of the new platform. We believe we are delivering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Words cannot describe the appreciation the entire neurology community has for Roger Rosenberg, MD, for his leadership of this journal over the past 2 decades. 1 Roger shepherded the journal through a number of important transitions including its title change, integration into The JAMA Network of publications, and move into the digital age with rapid online publication. For all intents and purposes, Roger was the journal for 20 years.…”
Section: S Andrew Josephson MDmentioning
confidence: 99%
See 1 more Smart Citation
“…Words cannot describe the appreciation the entire neurology community has for Roger Rosenberg, MD, for his leadership of this journal over the past 2 decades. 1 Roger shepherded the journal through a number of important transitions including its title change, integration into The JAMA Network of publications, and move into the digital age with rapid online publication. For all intents and purposes, Roger was the journal for 20 years.…”
Section: S Andrew Josephson MDmentioning
confidence: 99%
“…The report by Bongianni et al 1 in this issue of JAMA Neurology compares the results of cerebrospinal fluid (CSF) and nasal brushings as samples for the detection of misfolded prion protein using the latest refinement of the real-time quakinginduced conversion (RT-QuIC) test. Two earlier studies 2,3 reported test results of CSF and nasal brushings using a less refined RT-QuIC method on groups of patients with sporadic Creutzfeldt-Jakob disease (CJD) and patients with non-CJD neurologic and nonneurologic diseases.…”
Section: Paul Brown MDmentioning
confidence: 99%